A quadrature volume RF coil for vertical B0 field open MRI systems. Issue 3 (13th September 2016) - Tomanek, Boguslaw; Volotovskyy, Vyacheslav; Tyson, Randy; Yin, Donghui; Sharp, Jonathan; Blasiak, Barbara
Abstract: Cylindrical quadrature radio frequency (RF) coils are widely used in magnetic resonance imaging and spectroscopy due to their high sensitivity and field uniformity. However, the field geometry is unsuitable for use in low‐field open magnetic resonance imaging (MRI) systems with vertical B0 field configurations. Therefore, a new design is proposed. A quadrature RF coil that combines Alderman‐Grant and Helmholtz designs was constructed to produce two independent modes, both orthogonal to the main magnetic field. The coil provides good RF homogeneity over a 20 × 15 × 15 cm volume and operates as both a transmit and receive coil. The application of the coil for 0.2 Tesla permanent magnet with a vertical B0 field is shown. The proposed coil may be applied to MR imaging of larger objects at low vertical magnetic fields.